Staging and normal table of postembryonic development of the clownfish (Amphiprion ocellaris). Issue 7 (29th May 2019) - Roux, Natacha; Salis, Pauline; Lambert, Anne; Logeux, Valentin; Soulat, Olivier; Romans, Pascal; Frédérich, Bruno; Lecchini, David; Laudet, Vincent
Abstract: Background: The clownfish Amphiprion ocellaris is one of the rare coral reef fish species that can be reared in aquaria. With relatively short embryonic and larval development, it could be used as a model species to study the impact of global changes such as temperature rise or anthropogenic threats (eg, pollution) on the postembryonic development at molecular and endocrinological levels. Establishing a developmental table allows us to standardize sampling for the scientific community willing to conduct experiments on this species on different areas: ecology, evolution, and developmental biology. Results: Here, we describe the postembryonic developmental stages for the clownfish A. ocellaris from hatching to juvenile stages (30 days posthatching). We quantitatively followed the postembryonic growth and described qualitative traits: head, paired and unpaired fins, notochord flexion, and pigmentation changes. The occurrence of these changes over time allowed us to define seven stages, for which we provide precise descriptions. Conclusions: Our work gives an easy system to determine A. ocellaris postembryonic stages allowing, thus, to develop this species as a model species for coral reef fishes. In light of global warming, the access to the full postembryonic development stages of coral reef fish is important to determine stressors that can affect such processes. Key Findings: Seven developmental stages have been identified to describe the larval development of the clownfish Amphiprion ocellaris . Clownfish larvae undergo two distinct developmental growth phases that correspond to growth and metamorphosis. A dichotomous key determination has been created to assist users in identifying the various developmental stages.